Inhuman bondage : the rise and fall of slavery in the New World - Davis, David Brion (New York : Oxford University Press, 2006)
"Inhuman Bondage offers a compelling narrative that links together the profits of slavery, the pain of the enslaved, and the legacy of racism. It is the portrait of the dark side of the American dream. Yet it offers an inspiring example as well - the story of how abolitionists, barely a fringe group in the 1770s, successfully fought, in the space of a hundred years, to defeat one of human history's greatest evils."--Jacket.
The Amistad test of law and justice -- The ancient foundations of modern slavery -- The origins of antiblack racism in the New World -- How Africans became integral to New World history -- The Atlantic slave system : Brazil and the Caribbean -- Slavery in Colonial North America -- The problem of slavery in the American Revolution -- The impact of the French and Haitian revolutions -- Slavery in the nineteenth-century South I : from contradiction to defense -- Slavery in the nineteenth-century south II : from slaveholder treatment and the nature of labor to slave culture, sex and religion, and free Blacks -- Some nineteenth-century slave conspiracies and revolts -- Explanations of British abolitionism -- Abolitionism in America -- The politics of slavery in the United States -- The Civil War and slave emancipation.
Includes bibliographical references (pages 333-413) and index.
Keywords: Slavery -- United States -- History; Slavery -- America -- History; Antislavery movements -- United States -- History; Antislavery movements -- America -- History; Antislavery movements; Slavery; America; United States; Esclavage -- Histoire; Esclavage -- Histoire; Mouvements antiesclavagistes -- Histoire; Mouvements antiesclavagistes -- Histoire; Slavernij; Abolitionisme; Amerika; HISTORY / United States / Revolutionary Period (1775-1800); History; Nonfiction